Determining Some Chemical and Microbiological Changes in the Ripening Process of Kashar Cheese - Sevda Urçar Gelen; Mustafa Atasever; Özgür Kaynar (Turkish Journal of Agriculture: Food Science and Technology)
In the present study, some microbial, chemical, and physicochemical characteristics occurring during ripening were observed in unpackaged and vacuum-packed Kashar cheese samples. Some microbial and chemical properties of Kashar cheese samples were studied Also, the free fatty acid ratio was determined with the SDS-Page Electrophoresis to determine proteolysis during the ripening period and with the High-Performance Thin Layer Chromatography (HPTLC) for lipolysis. Physical, chemical, and microbiological analyzes were made at 0, 15, 30, 45, 60, and 75 days of ripening during which the changes in the number of microbiologically total aerobic mesophilic bacteria (TAMB), Lactobacillus spp., Lactococcus spp., Pseudomonas spp., yeast-mold, lipolytic, and proteolytic bacteria were determined. In the present study, % lactic acid, pH, dry matter percentage, color parameters (L, a and b values) and water activity (aw) were analyzed during ripening and the changes during storage were defined. Lactobacillus spp., Lactococcus spp., TAMB, and proteolytic bacteria counts and % lactic acid ratios were higher in vacuum-packed Kashar cheeses. It was found that lipolysis and proteolysis were higher in cheese samples stored open during ripening.